Growth of number of periodic orbits of one family of skew product maps. Issue 1 (2nd January 2018) - Esteves, Salete
ABSTRACT: In this article we introduce a one-parameter family of skew product ( G t ) t ∈ [−ε, ε] maps exhibiting a heterodimensional cycle such that the number of isolated periodic orbits inside it has not super-exponential growth. The dynamics in the central direction of the maps G t is described by a one-parameter family of system of iterated functions.